2002
DOI: 10.1590/s0074-02762002000400028
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Neuroschistosomiasis: Inadequacy of the Murine Model

Abstract: Neuroschistosomiasis is rarely observed in human pathology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Focal egg deposition and granulomatous encephalitis associated with convulsions were seen in an infected cercopithecus monkey (Cheever & Duvall 1974). Recently, Silva et al (2002) have called attention to the inadequacy of the murine model for studies concerning neuroschistosomiasis.…”
Section: Extrahepatic Pathologymentioning
confidence: 99%
“…Focal egg deposition and granulomatous encephalitis associated with convulsions were seen in an infected cercopithecus monkey (Cheever & Duvall 1974). Recently, Silva et al (2002) have called attention to the inadequacy of the murine model for studies concerning neuroschistosomiasis.…”
Section: Extrahepatic Pathologymentioning
confidence: 99%
“…Besides, this infection alters the level of nerve growth factor (NGF) and causes paw hyperalgesia. However, Silva LM et al [9] have reported different results and revealed the inadequacy of using mouse as an experimental model of NS. In fact, in as early as 1970, Jane JA et al [8] designed their experiments in different conditions, based on the aetiological possibilities of the direct or indirect pathways for NS, but the condition in the experiment was unlikely to occur during the nature course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although different from the nature course of infection, this method has several advantages. Firstly, the experimental course is greatly shortened, compared with percutaneous infection course (5-7 weeks) [8][9][10] , since it only takes 1-2 weeks to induce the NS granulomas in the acute stage of infection. Secondly, this method may help exclude many influencing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ex vivo samples had a catheter placed into the right heart and perfused by a fixative solution of 10% paraformaldehyde (PFA). The worm recovery was carried out as per the technique prescribed by Pellegrino and Siqueira [13][14][15][16][17][18].…”
Section: Mice and Infectionmentioning
confidence: 99%